GAYA HIDUP DALAM MENGONSUMSI SAYUR DAN BUAH SERTA TINGKAT KECUKUPAN GIZI ANAK USIA SEKOLAH DASAR DI KOTA METRO - Karina Ayesha; Yaktiworo Indriani; Begem Viantimala (Lampung University, 2020)
level, and factors affecting the consumption of vegetables and fruits in Metro City. The research is conducted purposely in Elementary School 1 Metro and Elementary School 6 Metro; involving 52 samples of 5th grade elementary school children obtained by using a simple random sampling method. Primary and secondary data were collected in November 2017 – May 2018. Vegetables and fruits consumption data were collected by 24-hour recall and analyzed descriptively by Variety of Nutritional Adequacy Value and statistically by multiple linear regression. The results showed that the nutritional adequacy level of elementary school students was as much as 82.69%, but they were experiencing deficiency of calcium and vitamin C. Average value of the variety of nutritional adequacy was 85%, which means that the food consumed by children is diverse. The lifestyle of elementary school students in consuming vegetables and fruits was indicated that they rarely bought various serving of vegetables and fruits since they like vegetables and fruits served at home. Elementary school students preferred local to import fruits and prefer buying them at traditional market to modern market. They agree that eating vegetables and fruits was important and had good impact on health. The factors which affect the consumption of vegetables and fruits were the number and types of vegetables and fruits consumed, the consumption frequency of vegetables and fruits, and the children’s opinion.Key words: fruits, lifestyle, nutritional adequacy level, vegetables